Valence Photoionization of Thymine: Ionization Energies, Vibrational Structure, and Fragmentation Pathways from the Slow to the Ultrafast. Issue 62 (14th October 2019) - Majer, Katharina; Signorell, Ruth; Heringa, Maarten F.; Goldmann, Maximilian; Hemberger, Patrick; Bodi, Andras
Abstract: The photoionization of thymine has been studied by using vacuum ultraviolet radiation and imaging photoelectron photoion coincidence spectroscopy after aerosol flash vaporization and bulk evaporation. The two evaporation techniques have been evaluated by comparison of the photoelectron spectra and breakdown diagrams. The adiabatic ionization energies for the first four electronic states were determined to be 8.922±0.008, 9.851±0.008, 10.30±0.02, and 10.82±0.01 eV. Vibrational features have been assigned for the first three electronic states with the help of Franck–Condon factor calculations based on density functional theory and wave function theory vibrational analysis within the harmonic approximation. The breakdown diagram of thymine, as supported by composite method ab initio calculations, suggests that the main fragment ions are formed in sequential HNCO‐, CO‐, and H‐loss dissociation steps from the thymine parent ion, with the first step corresponding to a retro‐Diels–Alder reaction. The dissociation rate constants were extracted from the photoion time‐of‐flight distributions and used together with the breakdown curves to construct a statistical model to determine 0 K appearance energies of 11.15±0.16 and 11.95±0.09 eV for the m / z 83 and 55 fragment ions, respectively. These results have allowed us to revise previously proposed fragmentation mechanisms and to propose a model for the final, nonstatistical H‐loss step in the breakdown diagram, yielding the m / z 54 fragment ion at an appearance energy of 13.24 eV. Abstract : When the thymine is right ! Exploring vaporization techniques, photoelectron spectra, potential energy surfaces, breakdown curves, and reaction mechanisms helps us to better understand nucleobases and their ion chemistry (see figure).